Growth and reproduction performance of Blackhead Persian sheep in Tanzania - Sendalo, D.S.C.; Das, S.M.; Mtenga, L.A. (1994)
Data collected at the livestock research centres, Malya and West Kilimanjaro, Tanzania, to determine the effects of genotype and environment on birth weight, weaning weight and weight at 24, 48, and 72 weeks of age were analysed. Records on the birth weight (n = 6207), weaning weight (n = 4444), weights at 24 weeks (n = 3494), 48 weeks (n = 2633) and 72 weeks of age (n = 1874) were evaluated for fixed effects: year of birth, season of birth, sex, birth type, age of dam and location of differences. The overall unadjusted mean weight at birth and weaning were 2.68 and 15.15 kg, respectively. The mean weights at 24, 48 and 72 weeks of age were 18.19, 22.93 and 33.24 kg respectively. Year had significant effect on birth weight, weaning weight and weights at 24, 48 and 72 weeks of age. Season also significantly influenced all weights except for birth weight and weight at 24 weeks of age. Birth type had significant effect on birth weight (P